PELATIHAN PENULISASN ARTIKEL DI JURNAL BEREPUTASI NASIONAL UNTUK GURU DI PROVINSI BENGKULU - Nidya dudija Dudija; Fetty Poerwita Sary; Adhi Prasetio; Ahmad Darajat Basallama (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
This community engagement initiative was prompted by the low rate of scientific publications by teachers in Bengkulu Province, particularly in accredited national journals, despite the fact that such publications are a key indicator of professionalism and career progression. The initiative aims to enhance teachers’ understanding and skills in writing scientific articles in accordance with academic standards. The training was conducted in-person through workshops and intensive mentoring, covering the following topics: understanding the structure of scientific articles; techniques for writing effective titles and abstracts; developing arguments based on literature; paraphrasing and avoiding plagiarism; using references and citations in APA style with the aid of the Mendeley application; strategies for selecting reputable journals; and practising article submission via an online system (OJS). Participants were primary, lower secondary, and upper secondary school teachers in Bengkulu Province, selected based on their readiness to undertake the programme. Evaluation results indicated a significant improvement in understanding of scientific writing, proficiency in using reference tools, as well as motivation and confidence in drafting and submitting articles to journals. This initiative contributed to fostering an academic culture among teachers and promoting the continuous improvement of publication quality. Recommendations for the future include strengthening the community of teacher-authors and providing consistent institutional support.  ABSTRAKKegiatan pengabdian masyarakat ini dilatarbelakangi oleh rendahnya tingkat publikasi ilmiah guru di Provinsi Bengkulu, khususnya pada jurnal nasional terakreditasi, padahal publikasi menjadi indikator penting profesionalisme dan kenaikan pangkat. Kegiatan ini bertujuan meningkatkan pemahaman dan keterampilan guru dalam menulis artikel ilmiah sesuai standar akademik. Pelatihan dilaksanakan secara luring melalui workshop dan pendampingan intensif dengan materi meliputi: pemahaman struktur artikel ilmiah, teknik penulisan judul dan abstrak yang efektif, pengembangan argumen berbasis literatur, parafrase dan penghindaran plagiarisme, penggunaan referensi dan sitasi berbasis APA Style dengan bantuan aplikasi Mendeley, strategi pemilihan jurnal bereputasi, serta praktik submit artikel melalui sistem daring (OJS). Peserta merupakan guru SD, SMP, dan SMA di Provinsi Bengkulu yang diseleksi berdasarkan kesiapan mengikuti program. Hasil evaluasi menunjukkan peningkatan signifikan pada pemahaman penulisan ilmiah, keterampilan penggunaan tools referensi, serta motivasi dan kepercayaan diri dalam menyusun dan mengirimkan artikel ke jurnal. Kegiatan ini berkontribusi dalam membangun budaya akademik guru dan mendorong peningkatan kualitas publikasi secara berkelanjutan. Rekomendasi ke depan mencakup penguatan komunitas penulis guru dan dukungan institusional yang konsisten.